Biofilm Formation in Dairy: A Food Safety Concern—Biofilms in the milking machine, from laboratory scale to on-farm results - Chloé Desmousseaux; Morgan Guilbaud; Gwenaëlle Jard; Hélène Tormo; Nadia Oulahal; Aurélie Hanin; Erwan Bourdonnais; Piyush Kumar Jha; Cécile Laithier (Journal of Dairy Science)
ABSTRACT: Raw milk is known to harbor a complex microbial community, including microorganisms of technological and human health interest. However, it can also be a source of pathogenic and spoilage bacteria, such as spore-forming bacteria and Pseudomonas spp. Despite cleaning and disinfection procedures, biofilms in milking machines are difficult to remove and represent a major source of milk contamination. This work aims to describe biofilms in milking machines at both the laboratory and farm scales. Encouraging studies on the microbiota of milking machine biofilms, the parameters influencing changes in biofilm composition, and the methods used to characterize them are essential for managing the formation and composition of these biofilms. Enhancing such knowledge will help improve the understanding of milking machine biofilms and their impact on the quality of milk and dairy products.